Comparative Analysis of Business Income Levels Before and After Having A Halal Certificate Small Entrepreneurs in Serang City - Yuda Supriatna; Amarul Amarul (University of Science and Computer Technology, 2023)
Study This aim for analyze comparison is there Analysis comparison level income business before and after own halal certificate for entrepreneurs small town in Serang City. Research result This expected can made reference by stakeholders policy especially related ones with internal halal certificate do socialization to entrepreneurs small, so the program is medium run by the government on a halal certificate program in frame increase quality and consumers' sense of security. Research methods used is method comparative that is compare second variable the results study with the